On the notion of suffering in the Bribri indigenous population - Arroyo Araya, Helga (2026)
Introduction: This article is part of the research of the School of Psychology of the University of Costa Rica «Memory, struggle, and resistances of the Bribri Indigenous people», which was developed in articulation with the Th Bribri Indigenous Territorial Government Association (ADITIBRI), the Indigenous Women of Talamanca Association (ACOMUITA), the Local Instance for the Integral Approach to Suicide (ILAIS-Talamanca). Objective: It seeks to situate the notions of suffering from the Bribri indigenous Cosmovision, to establish new dimensions of understanding, respectful of how reality is interpreted. This is relevant because it offers an epistemological framework from the Bribri indigenous knowledge, vital for approaches that detach themselves from the matrix of coloniality of power. Method: From a qualitative approach, the conception of suffering is constructed through the narratives of seven Bribri indigenous leaders. Discourse analysis was used as a method for the analysis of these texts. Results: The findings obtained point to conceptualizing suffering from four places of meaning: suffering as disconnection, suffering as an external cause of damage, suffering as a collective affectation, and suffering as a subjective experience and experience. Conclusions: There is a relationship between the idea of affectation of the power to act by an external cause, which provokes a wound in the indigenous being and in the spatiotemporal order that gives meaning to their existence as Bribris. Suffering cannot be located only in the individual affectation but must have a correspondence with the collective.